2020
DOI: 10.1016/j.purol.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

When residents work less, they feel better: Lessons learned from an unprecedent context of lockdown

Abstract: Introduction With the COVID-19 outbreak activities of urology departments have been limited to non-deferrable procedures impacting the daily program of residents in urology. We assessed the psychological impact of the lockdown on Belgian residents in urology and their resounding on the quality of the training. Material and Methods A self-administered anonymous questionnaire assessing the risk of burnout in a pandemic situation and its impact on the quality of the traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
(14 reference statements)
0
18
1
1
Order By: Relevance
“…However, middle-aged and older adults were notably more likely than younger participants to report no change; hence, the mitigation measures appear to have affected the quality of life of younger Austrians more than other age groups, both positively and negatively. That these effects on quality of life might differ depending on age was recently corroborated by a Belgian survey among young physicians, where 56% reported a positive impact of the COVID-19 crisis on their life (Degraeve et al 2020 ).…”
Section: Discussionmentioning
confidence: 82%
“…However, middle-aged and older adults were notably more likely than younger participants to report no change; hence, the mitigation measures appear to have affected the quality of life of younger Austrians more than other age groups, both positively and negatively. That these effects on quality of life might differ depending on age was recently corroborated by a Belgian survey among young physicians, where 56% reported a positive impact of the COVID-19 crisis on their life (Degraeve et al 2020 ).…”
Section: Discussionmentioning
confidence: 82%
“…Since the onset of the COVID-19 pandemic several studies have investigated its impact on the occurrence of burnout in medical residents showing a wide range of prevalence, between 26% and 76%. 15 , 16 This may be due to the heterogeneity of the studies conducted, for example, using different burnout 17 , 18 assessment scales. Some of the studies found higher prevalence depending on the number of COVID-19 patients seen.…”
Section: Stress and Burnout During Residencymentioning
confidence: 99%
“… 12 , 13 Data from Rodrigues et al (2018) 14 show that prevalence was higher in surgical and emergency specialties (40%) compared to medical specialties (25%). In relation to other factors, it has been described that both the first year and the last year of residency, 24 other recent stressful events 15 , 28 and dissatisfaction with the chosen specialty 12 , 23 constitute risk factors for burnout ( Table 1 , Table 2 ).…”
Section: Individual and Psychosocial Factors Related To The Occurrence Of Stress And Burnout Syndrome During Residencymentioning
confidence: 99%
“…Forty-four articles finally matched the search. Twenty-one were comments/editorials/reviews broadly describing changes in residency programs during the pandemic, mostly published during the very initial phase of the outbreak 626 ; some of them focused also on perspectives toward digital education and e-learning opportunities. 711,20,24 Four articles highlighted the viewpoint of medical students and urology applicants, 2730 impaired by the reduced opportunity for rotations.…”
Section: Resultsmentioning
confidence: 99%